2013
DOI: 10.5402/2013/246737
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fat-Soluble Vitamins A and D in the Pathogenesis of Influenza: A New Perspective

Abstract: Reduced exposure to solar radiation, leading to a de�ciency of vitamin D and hence impaired innate immunity, has been suggested as a trigger for in�uen�a viral replication and as an explanation of seasonal in�uen�a. Although this hypothesis accounts for many unexplained facts about the epidemiology of in�uen�a, gaps remain in understanding the pathogenesis and manifestations of the disease. Several observations suggest a role for vitamin A compounds (retinoids) in the disease. is paper presents a new model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 214 publications
(253 reference statements)
0
14
0
1
Order By: Relevance
“…The active form of vitamin D, also known as calcitriol (1,25-dihydroxycholecalciferol) is a steroid hormone that acts as an immune system modulator by down-regulating the expression of inflammatory cytokines and enhancing macrophage function [6]. Furthermore, it induces the expression of potent antimicrobial peptides (AMPs), which are present in natural killer cells, monocytes, neutrophils, as well as the epithelial cells lining the respiratory tract 13 . Vitamin D triggers development of suppressive regulatory T cells and inhibits development of pro-inflammatory Th17 cells 14 .…”
Section: Vitamin D As An Immunemodulator Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The active form of vitamin D, also known as calcitriol (1,25-dihydroxycholecalciferol) is a steroid hormone that acts as an immune system modulator by down-regulating the expression of inflammatory cytokines and enhancing macrophage function [6]. Furthermore, it induces the expression of potent antimicrobial peptides (AMPs), which are present in natural killer cells, monocytes, neutrophils, as well as the epithelial cells lining the respiratory tract 13 . Vitamin D triggers development of suppressive regulatory T cells and inhibits development of pro-inflammatory Th17 cells 14 .…”
Section: Vitamin D As An Immunemodulator Factormentioning
confidence: 99%
“…Moreover, the pro-inflammatory peptides of the adaptive immune system are modulated by vitamin D, particularly those involved in acute inflammation cytokine storms 9,11,13,15 . It has also been found that metabolites of vitamin D induce other innate antimicrobial effector mechanisms, including autophagy and synthesis of reactive oxygen and nitrogen intermediates 11 .…”
Section: Vitamin D As An Immunemodulator Factormentioning
confidence: 99%
“…Vitamin D is a steroid hormone and an immune system modulator, which lowers the expression of inflammatory cytokines in addition to increasing the macrophage activity. It also promotes the expression of antimicrobial peptides (AMPs) that are present in natural killer cells, monocytes, neutrophils, and epithelial cells lining the respiratory tract (23). Vitamin D acts both by suppressing and defending against infection by increasing anti-pathogen peptides.…”
Section: Vitamin D (Ergocalciferol)mentioning
confidence: 99%
“…73 It further blocks the production of T-helper 17 cells (proinflammatory) and induces the production of suppressive regulatory T cells. 74 Furthermore, the proinflammatory peptides associated with the adaptive immune system, especially the ones involved in acute inflammatory cytokine storm, are regulated by vitamin D. 70,73,75 Numerous epidemiological studies have demonstrated the potential link between deficiency of vitamin D in the body and enhanced risks of respiratory tract infections. 76,77 Also, many studies reveal the protective role of vitamin D supplementation against virus mediated infections.…”
Section: Role Of Vitamin D On Covid-19 Infectionmentioning
confidence: 99%